Rancang Bangun Aplikasi Carikerja di Pusat Karir Institut Teknologi Garut Berbasis Android - Ridwan Setiawan; Yoga Handoko Agustin; Mohamad Fikri Haekal; Leni Fitriani (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
The Career Development Center of Institut Teknologi Garut is an educational and training institution for students and alums of the Garut Institute of Technology. Career Center plays a role for students or graduates in conducting job searches and being an information liaison between companies and students or graduates when there is information on job vacancies. This research aims to design the CariKerja application as a direct link between students or graduates and companies and to assist the Garut Institute of Technology's career center in finding job vacancies. The methodology used in software engineering is the Rational Unified Process (RUP) methodology with the stages used, namely inception, elaboration, construction, and transition, with Unified Modeling Language (UML) modeling with use case diagrams, activity diagrams, sequence diagrams, and sequence diagrams. The result of this research is that the application can interact directly between students or graduates with companies. Students or graduates can apply for job applications, and companies can create job vacancies with independent management. The unique feature of this application is the curriculum vitae (cv) generator, where when the alums do not have a CV or renew their CV, this feature can help make a CV based on the template provided.